MORPHOLOGICAL CHARACTERISTICS OF LUNG TISSUE IN CASES OF DEATH AT THE SCENE OF A TRAUMATIC BRAIN INJURY - Masharipov, A.S.; Israilov, R. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To improve the quality and evidence of expert findings on death from traumatic brain injury (TBI) in hospitals in cases of complications from the respiratory system. Material and Methods: 140 cases of severe traumatic brain injury were analyzed when the time of injury and death was known, since the main criterion for studying the morphological changes of the lungs was the time of death at the scene of traumatic brain injury. Results: Deaths of inpatients at various stages of experiencing a closed head injury, in contrast to deaths due to head injury at the scene, are characterized by features of the morphological changes of the lungs, represented by a sequential change in the processes of circulatory disorders and pulmonary ventilation, inflammation. Conclusions: Deaths of victims at various stages of experiencing a closed craniocerebral injury are characterized by features of the morphological changes of the lungs, represented by a sequential change in the processes of circulatory disorders and pulmonary ventilation, inflammation.